Assessing functional suitability of a lyophilized formulation containing designed ankyrin repeat proteins for radionuclide imaging of HER2/neu overexpression in malignant tumors - R. N. Varvashenya; A. A. Prach; E. V. Plotnikov; S. M. Deev; M. V. Belousov; M. S. Larkina; V. I. Chernov (Бюллетень сибирской медицины, 2024)
Aim. To study in vitro and in vivo the functional suitability of 99mTc-labeled lyophilized formulation containing designed ankyrin repeat protein (DARPin) G3-(GGGS)3Cys for radionuclide imaging of HER2/neu overexpression in malignant tumors.Materials and methods. To create a targeted protein, a modified genetic construct with the sequence encoding DARPin G3-(GGGS)3Cys was used. To generate the experimental probe, we used a lyophilized formulation containing DARPin G3-(GGGS)3Cys with auxiliary substances and 99mTc sodium pertechnetate (500 MBq) incubated at 60 °C for 30 min. Radiochemical purity of 99mTc-G3-(GGGS)3Cys was analyzed by thin-layer radiochromatography. SKOV-3, BT-474, and DU-145 cell lines were used to test binding specificity in vitro. The dissociation constant was determined via a saturation binding assay on SKOV-3 cells with a range of protein concentrations from 0.2 to 40 nM. Nu/j mice bearing HER2-positive SKOV-3 xenografts and HER2-negative Ramos xenografts were used to evaluate the targeting properties and biodistribution.Results. A radiocomplex based on 99mTc and a lyophilized formulation with DARPin G3-(GGGS)3Cys was obtained with the radiochemical purity of more than 96%. Binding of 99mTc-G3-(GGGS)3Cys to the cells was specific (KD 3.9 ± 0.5 nM) and proportional to the level of HER2/neu expression in the cells. The uptake of 99mTc-G3-(GGGS)3Cys in SKOV-3 xenografts was significantly higher than in Ramos xenografts. 99mTc-G3-(GGGS)3Cys demonstrated rapid blood and renal clearance and had low activity in the salivary glands and stomach. Liver uptake was about 5–7%ID/g. In addition, 99mTc-G3-(GGGS)3Cys exhibited very low uptakes in the lungs, muscles, small intestine, and bones.Conclusion. The 99mTc-labeled lyophilized formulation with DARPin G3-(GGGS)3Cys is functionally suitable for imaging HER2/neu overexpression in tumors, as it binds specifically to the receptor, is stable in vivo, and has favorable biodistribution in organs and tissues. The radiocomplex based on 99mTc-G3-(GGGS)3Cys was obtained by a simple method with high radiochemical purity.